Quantifying lateral and intratidal variability in water level and velocity in a tide‐dominated river using combined RTK GPS and ADCP measurements. (1st May 2014) - Matte, Pascal; Secretan, Yves; Morin, Jean
<x xml:space="preserve">Abstract</x> Cross‐sectional gradients in water levels and velocities play a determining role in the circulation dynamics of tidal rivers and estuaries. Documenting and analyzing their variability throughout a tidal cycle require observations with high spatial and temporal resolution. A survey strategy and a data analysis procedure have been designed to obtain continuous and synoptic water level and velocity fields over a tidal cycle, along 13 cross‐sections of the St. Lawrence fluvial estuary dominated by large tidal ranges. The method combines both RTK GPS and ADCP technologies for the simultaneous measurement of water levels and velocities along repeated boat transects, allowing fast data acquisition over wide river sections and under rapidly changing conditions. The reconstruction of continuous and synoptic fields is made by interpolation. Simplifying assumptions about data stationarity and/or homogeneity are avoided by adapting the interpolation procedures to the shape and distribution of the underlying data in a space‐time reference frame, thus minimizing distortion in the reconstructed quantities. The capabilities and limitations of the method are assessed through error computations and comparisons with alternate data analysis methods and complementary data sets from tide gauges. With these latest observations, new insights into the tidal hydrodynamics of the St. Lawrence fluvial estuary are gained in regions of contrasting tidal and fluvial properties, specifically related to the effects of channel curvature and bathymetry on tidal propagation and cross‐channel flow properties at the intratidal scale.